Outbreaks of rhinoceros beetle (oryctes rhinoceros) on oil palm plantations selected area at Keratong 3, Pahang / Muhammad Jabrullah Badrul Hisham - Badrul Hisham, Muhammad Jabrullah (Faculty of Plantation and Agrotechnology, 2017)
Oil palm Elais guinensis is the large scale tree planted in Malaysia, human population that increasing rapidly has force the supplied food increasing their production, daily use of oil palm in food production make the oil palm hard to replace with other source of oil. The rhinoceros beetle attack lead to oil palm drop in production of yield, physically damage and lead to unproductive plant, attack from this coleopteran pest in oil palm industry has make this beetle become major pest for oil palm plantations. The research questionnaires were conducted via face to face interview to 132 respondents. The objective of this study are to determine the awareness of farmers regarding the damage of oil palm by rhinoceros beetle and to evaluate the best current control strategy that implement by farmers. Results from the study indicate that mostly of respondent’s belong to male farmers with age around 30-39 years old with annual income around RM 1,000 to RM 1,999 per month. As for the educational levels, respondents were mainly having the high school level of education and having one to five year experience in handling the field. As a result, significant difference between educations and knowledge about rhinoceros beetle attacks (0.023). The results show that the different level of education, it will influence the farmer’s knowledge about rhinoceros beetle attacks. Besides that, the result also showed that they is significant different between pesticide applications with gender of farmers (0.017). Significant shows that the different gender of farmers practices different pesticide applications. Respondents are understood and aware about the rhinoceros beetle attacks and its effects. Farmers need to take seriously about this matter since it will affect yield and growth performance of oil palm tree.